Self-perceived pain levels following irrigation with various concentrations of sodium hypochlorite solution and gels: A systematic review of randomized clinical studies - Altuhafy, Maryam; Askar, Ghida; Jabr, Luay; Zegar, Zegar; Khan, Junad (International Journal of Dental Materials, 2024)
Background: Sodium hypochlorite, a prevalent root canal irrigation solution, valued for its antibacterial properties and tissue-dissolving abilities, varies in concentration (0.5% to 8.25%). However, its efficacy across formulations awaits systematic evaluation.Aim: To evaluate self-perceived post-operative pain levels in a 5.25% concentration of NaOCl in gel or solution form.Materials and Methods: An unrestricted search of indexed databases (PubMed, Embase, Scopus, Web of Science, and Cochrane) and a manual search were performed up to April 2023. Three randomized controlled trials (RCTs) compared a solution form of 5.25% NaOCl to other solution concentrations, whereas 2 RCTs compared a gel form of 5.25% NaOCl concentration to 5.25% NaOCl solution form. The risk of Bias (RoB) assessment was conducted using the Cochrane tool.Results: A total of 5 RCTs met the inclusion criteria and were included in the review. Four RCTs used the visual analog scale (VAS), whereas 1 RCT used the numeric rating scale (NRS) to assess post-operative pain. Three RCTs had a moderate Risk of Bias (RoB), whereas 1 had a low and 1 had a high RoB.Conclusion: Based on the current evidence the concentration of NaOCl used during irrigation did not have any effect on the post-operative pain developed regardless of the use of a gel or solution forms. Future randomized studies with standardized protocols are needed to further investigate the efficacy of NaOCl concentration on postoperative pain in endodontic treatment.